"It will be a weapon in my hand": The Protective Potential of Education for Adolescent Syrian Refugee Girls in Lebanon - Garbern, Stephanie Chow; Helal, Shaimaa; Michael, Saja; Turgeon, Nikkole J.; Bartels, Susan (Refuge, 2020)
This study uses over 140 first-person narratives from adolescent Syrian girls and Syrian parents displaced to Lebanon and literature from the Education in Emergencies (EiE) field to examine the concept of the protective potential of education. The findings illustrate the interplay between the risks taken to obtain education versus the protective potential of education for this vulnerable group. For this study population, protection risks frequently outweighed the protective potential of education and ultimately influenced decision-making at the individual level on continuation of education in Lebanon.